Basic Taxation Outreach to Community Empowerment Institution (LPM) in Rempoa Sub-District, South Tangerang - Lukmanul Hakim; Ghea B Astrid Sunanto (Abdimas Paspama, 2025)
This community service activity aims to increase tax awareness among members of the Community Empowerment Institution (LPM) in Rempoa, South Tangerang. Many small business actors still lack fundamental knowledge about taxation, which leads to low tax compliance and reporting errors. The program provided structured socialization and training, including basic taxation concepts, financial recording practices, and e-filing using the Directorate General of Taxes (DJP) Online system. Through lectures, tutorials, and interactive discussions, participants were guided to understand their tax obligations and how to fulfill them independently. The results show a significant improvement in the participants’ ability to perform basic tax calculations, financial documentation, and online reporting. This initiative is expected to promote voluntary tax compliance and support sustainable economic development at the local level. Furthermore, it demonstrates that empowering MSMEs with tax literacy can be an effective strategy to enhance state revenue and build a tax-compliant culture in Indonesia’s grassroots economy.